HAI : an instructional motion graphic of how to interact with people with Autism for grade-schoolers / Fonita Theresia Yoliando - Yoliando, Fonita Theresia (Universiti Teknologi MARA, Perak, 2020)
Autism Spectrum Disorder (ASD) is known as 'triad impairment' which consists of communication, interaction, and behaviour problem. They also exhibit hypersensitivities or hyposensitivities to physical sensory stimuli which affect the processing system to be overloaded and cause an uncomfortable feeling or pain. Their reactions then trigger some particular behaviors, which are considered aggressive, harmful, repetitive, and odd. The main problem is most people judge and avoid them solely based on their actions without any effort to find out the reason and learn how to interact with them properly. This one-sided stereotype most probably leads them and their family to emotional insecurities, lack of self-esteem, and rebellious tendency. While this kind of situation is mostly centralized, institutionalized, and deep rooted in society, it can be reconditioned through a small step by teaching people since their early age the appropriate way to interact with people with autism. It is essential to realize that each individual with autism is first and foremost an individual who should not be treated as invisible in society. In order to facilitate this idea, I offer HAI: An Instructional Motion Graphic of How to Interact with People with Autism for Grade Schoolers which consists of several illustrated empirical steps which can be applied in school. The instructions are suitable to interact with several specific types of ASD, such as Classic Autism and Asperger syndrome, by reason of the severity of the symptoms which enables them to live relatively normal lives in society. In other words, the main objective of this project is to encourage and assist people, especially grade schoolers to have short conversation or simple interaction with their autistic friends through practical and proper set of actions. Throughout this project, sequential exploratory design method was implemented by combining qualitative and quantitative method in the process